Some Results on Perturbation of Duality of OPV-Frames - Sharma, R.
In this paper, we consider a perturbation of operator-valued frames (OPV-frames) and obtain conditions for their stability in terms of operators associated with the OPV-frames.Also, some duality relations of OPV-frames are discussed. Fi-nally, some properties of the duals of OPV-frames are proven.
Keywords: Mathematics